An experimental study of attitudes to changing water charges in Scotland - Cameron A. Belton; Deidre A. Robertson; Pete Lunn (The Economic and Social Research Institute (ESRI), 2020)
If an aim of a regulatory body is to act on behalf of the views of its citizenry, then it is important to understand what those views are. This paper, in collaboration with the OECD and the Scottish water industry, presents the results of an online (n= 500) and face-to-face laboratory (n= 100) study that utilised experimental behavioural science to explore how the provision and presentation of future price change information influences Scottish citizens' acceptance of water price changes. Participants were asked to rate different patterns of price rises for their water charges. The pattern, presentation, magnitude of price rises and the provision of additional cost information (designed to simplify the calculations of future costs) was manipulated across tasks and participants. Results from this study suggest that Scottish citizens are generally accepting of price rises in the short and medium terms. However, the patterns of price rises, and the way in which information is presented, can influence these attitudes, suggesting that consumers do not always accurately integrate sequential price rises over time. Findings from this study are designed to inform the regulatory process of the Scottish water industry and highlight the potential role of behavioural science in regulation more generally.
Keywords: 330; Wasserpreis; Experiment; Befragung